The Analysis of Organic Dry Lettuce (Lactuca sativa L) Supply Chain at CV. Artha Krina Denpasar, Bali - Putu Fajar Kartika Lestari; I Made Tamba; Tengku Ramadan Syah (Warmadewa University Press, 2025)
Organic curly lettuce is one of the products in the organic market with increasing demand due to growing awareness of healthy lifestyles and environmental sustainability. Supply chain management activities are carried out to add value to the products offered and in turn, directly enhance the company's competitiveness. A well managed supply chain can increase the company product sales and improve customer satisfaction by delivering high quality products at low costs, accompanied by fast and responsive service. This study aims to analyse the supply chain performance of organic curly lettuce (Lactuca sativa L) at CV Artha Krina Denpasar, Bali, using the Supply Chain Operations Reference (SCOR) method. The analysis includes supply chain mapping, performance measurement based on SCOR attributes, and identification of constraints and potential solutions. The results showed that supply chain performance has generally met most of the specified indicators, such as delivery speed and flexibility. However, there is still room for improvement, especially in order fulfilments which was recorded at 77.7%, which is below the optimal category. supply chain activities at CV Artha Krina involve the flow of supplies from local farmers as the main supplier. If the supply from farmers is insufficient or does not meet the standards set by the company, CV Artha Krina will make purchases from the market as an alternative to meet customer needs. Seasonal factors and distribution constraints are key challenges that need to be managed to support the company's competitiveness. Supply chain mapping shows that CV Artha Krina has implemented an integrated system with local farmers and markets as suppliers, and hotels and villas as the main consumers. The results showed that the delivery performance: 100% (superior category). Supply Chain Flexibility: 3 days (superior category). Total Cost of Product Delivery: 57.14% (low category). Optimizing Order Fulfilments in a way that CV Artha Krina needs to increase cooperation with farmers to ensure product availability throughout the year. Regarding Logistics improvement CV Artha Krina requires investment in refrigeration and packaging technology to maintain product freshness during distribution